Even in correctable search, some types of rare targets are frequently missed - Van Wert, Michael J. (2009)
Socially important visual search tasks, such as airport baggage screening and tumor detection, place observers in situations where the targets are rare and the consequences of failed detection are substantial. Recent laboratory studies have demonstrated that low target prevalence yields substantially higher miss errors compared to high prevalence conditions when the same targets appear frequently (Wolfe, Horowitz, & Kenner, 2005; Wolfe et al., 2007). Under some circumstances, this "prevalence effect" can be eliminated simply by allowing observers to correct their last response (Fleck & Mitroff, 2007). However, in three experiments involving search of realistic x-ray luggage images, we find that the prevalence effect is not eliminated either by giving observers the choice to correct a previous response or by requiring observers to confirm their responses. This prevalence effect, obtained when no trial by trial feedback was given, was smaller than the effect obtained when observers searched through the same stimuli but were given trial by trial feedback about accuracy. We suggest that low prevalence puts pressure on observers in any search task, and that the diverse symptoms of that pressure manifest themselves differently in different situations. In some relatively simple search tasks, misses may result from motor or response errors. In other more complex tasks, shifts in decision criteria appear to be an important contributor.